Assessment and Autonomy in Language Learning
XIV, 223 p.
Keywords: This book examines this contested relationship between assessment and autonomy from a number of perspectives in a variety of Higher Education language-learning contexts in Europe and the Far East. The contributors to the book describe research into assessment both for and as autonomy, as well as approaches to the assessment of autonomy itself.